Anode with double layers for use in lithium ion batteries

By using the two-layer anode active material design of silicon and graphite in the anode of lithium-ion batteries, the shortcomings in energy density and cycle stability of existing lithium-ion batteries are solved, and higher specific capacity and longer service life are achieved.

CN119836693APending Publication Date: 2025-04-15APPLE INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380060810.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-08-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in terms of high volume energy density and discharge-charging cycles, which are difficult to meet the demand for higher energy density and longer life batteries for consumer electronic products.

Method used

An anode with two layers of anode active material is adopted, the first layer is made of silicon and the second layer is made of graphite, and these layers are arranged on the anode current collector to optimize the performance of the anode through different binder ratios and combinations.

Benefits of technology

Through the design of the second layer anode active material, the specific capacity and cycle stability of the battery are significantly improved, the service life of the battery is extended, and the discharge capacity is maintained at high cycle times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836693A_ABST
    Figure CN119836693A_ABST
Patent Text Reader

Abstract

The present disclosure relates generally to battery cells, and more particularly, to an anode active material comprising two layers for use in lithium ion battery cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates generally to battery cells, and more particularly, to an anode having two layers of anode active material for use in a lithium ion battery cell. Background Art

[0002] Lithium-ion (Li-ion) batteries are widely used as power sources in consumer electronic products. Consumer electronic products require Li-ion batteries that can provide higher volumetric energy density and sustain more discharge-charge cycles. Summary of the invention

[0003] In a first aspect, the present disclosure relates to an anode comprising an anode current collector, a first layer disposed on the anode current collector, and a second layer disposed on the first layer. The first layer comprises silicon, and the second layer comprises graphite. The first layer and the second layer together can be considered an anode active material.

[0004] In some variations, the anode current collector includes copper or nickel. In some variations, the anode current collector is copper, such as copper foil. In some variations, the anode current collector is nickel, such as nickel foil. In some variations, the anode current collector is a carbon-coated copper foil. In some variations, the anode current collector is a carbon-coated nickel foil. In some variations, the first layer may be 5%-60% by weight of the total weight % of the first and second layers. In some variations, the first layer is 10%-30% by weight of the total weight % of the first and second layers. In further variations, the first layer is 15%-25% by weight of the total weight % of the first and second layers.

[0005] In a second aspect, the first layer includes a first binder. In some variations, the amount of the first binder is 5% by weight to 15% by weight of the first layer. In some variations, the first binder is selected from polyacrylic acid (PAA), polyimide (PI), polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyethyleneimine (PI), polyurethane (PU), their derivatives, their copolymers and their combinations. In further variations, the first binder is polyurethane. The first layer may also include carboxymethyl cellulose (CMC). In further variations, the first layer may include carbon nanotubes. In further variations, the first layer may include carbon black.

[0006] In a third aspect, the second layer includes a second binder. In some variations, the amount of the second binder is 1 wt % to 10 wt %. In some variations, the second binder is selected from a combination of styrene-butadiene rubber (SBR), CMC, and SBR and CMC. In a further variation, the second binder is a combination of SBR and CMC. In some variations, the amount of SBR is 0.5 wt %-5 wt %. In some variations, the amount of CMC is 0.5 wt %-5 wt %. In a further variation, the second layer includes carbon black.

[0007] In a fourth aspect, a battery cell includes a cathode having a cathode active material disposed on a cathode current collector and an anode as described herein; a separator disposed between the cathode and the anode; and an electrolyte fluid disposed between the cathode and the anode. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] The present disclosure will be readily understood through the following detailed description in conjunction with the accompanying drawings, in which like reference numerals represent like structural elements, and in which:

[0009] Figure 1 is a top-down view of a battery cell according to an exemplary embodiment;

[0010] Figure 2 is a side view of a set of layers of a battery cell according to an exemplary embodiment;

[0011] Figure 3A is a side view of an anode according to an exemplary embodiment, the anode including an anode current collector, a first layer including a silicon-containing active material disposed on the anode current collector, and a second layer including graphite disposed on the first layer;

[0012] Figure 3B is a side view of a copper foil anode current collector and a single layer including both a silicon-containing active material and graphite disposed on the anode current collector according to an exemplary embodiment;

[0013] Figure 4 depicts the cycling performance of an anode having a first silicon-containing layer disposed thereon and a second graphite-containing layer disposed on the silicon-containing layer in accordance with an exemplary embodiment compared to silicon and graphite combined in a single layer;

[0014] Figure 5A depicts a scanning electron microscope (SEM) image of a first silicon-containing layer disposed on a copper anode current collector and a second graphite-containing layer disposed on the silicon-containing layer according to an exemplary embodiment;

[0015] Figure 5Bdepicts a SEM image of an anode according to an exemplary embodiment, the anode comprising an anode current collector and a single layer comprising both silicon and graphite disposed on the anode current collector;

[0016] Fig. 6A depicts an SEM image of a graphite-containing layer without any silicon-containing particles according to an exemplary implementation;

[0017] Figure 6B depicts an SEM image of a single layer of both combined graphite and silicon-containing particles according to an exemplary embodiment;

[0018] Fig. 7A depicts a scanning electron microscope image of carbon nanotube particles disposed in a single layer of a silicon-containing active material according to an exemplary embodiment;

[0019] Figure 7B depicts a scanning electron microscope image of carbon nanotube particles disposed in a layer comprising combined silicon and graphite according to an exemplary embodiment;

[0020] Fig. 8A Depicted is capacity retention as a function of cycle count for two cells according to an exemplary embodiment: a first cell having an anode having a first silicon-containing layer disposed on the anode and a second graphite-containing layer disposed on the silicon-containing layer; and a second cell having a single layer of combined silicon and graphite disposed on the anode;

[0021] Figure 8B Depicted is capacity retention as a function of cycle count for two cells according to an exemplary embodiment: a first cell having an anode having a first silicon-containing layer disposed on the anode and a second graphite-containing layer disposed on the silicon-containing layer; and a second cell having a single layer of combined silicon and graphite disposed on the anode; and

[0022] Fig. 9 The discharge capacity over 100 cycle counts is shown for the following three batteries according to exemplary embodiments: battery 902 having an anode having a first silicon-containing layer disposed on the anode and a second graphite-containing layer disposed on the silicon-containing layer; battery 904 having only the silicon-containing layer; and battery 906 having only the graphite layer. DETAILED DESCRIPTION

[0023] Reference will now be made in detail to the representative embodiments illustrated in the accompanying drawings. It should be understood that the following description is not intended to limit the embodiments to a preferred embodiment. On the contrary, it is intended to cover alternatives, modifications and equivalents that may be included in the essence and scope of the described embodiments defined by the appended claims.

[0024] The present disclosure relates to an anode, which includes an anode current collector, a first layer disposed on the anode current collector, and a second layer disposed on the first layer. The first layer contains silicon (also referred to herein as a "silicon-containing layer"). Silicon may also be referred to as a "silicon-containing active material". The second layer contains graphite (also referred to herein as a "graphite-containing layer").

[0025] In certain variations, the first layer disposed on the anode current collector is a graphite-containing layer, and the second layer is a silicon-containing layer. In such variations, the graphite-containing layer may include any additional components in any amount as described herein for the graphite-containing layer. Similarly, the silicon-containing layer may include any component in any amount as described herein.

[0026] Different layers of silicon and graphite may contain different binders. In various aspects, the binder may help maintain contact between particles, thereby allowing for increased conductivity. In variations, the binder in the silicon-containing layer may have stronger adhesion / cohesion than the binder in the graphite-containing layer. Further, the silicon-containing layer may contain a greater amount of binder than the graphite-containing layer.

[0027] Figure 1 A top-down view of a battery cell 100 according to one embodiment is presented. The battery cell 100 may correspond to a lithium ion or lithium polymer battery cell for powering devices used in consumer, medical, aviation, defense, and / or transportation applications. The battery cell 100 includes a stack 102 having a plurality of layers, the plurality of layers including a cathode having a cathode active coating, a separator, and an anode having an anode active coating. More specifically, the stack 102 may include a strip of cathode active material (e.g., an aluminum foil coated with a lithium compound) and a strip of anode active material (e.g., a copper foil, a nickel foil, a copper foil coated with carbon, or a nickel foil coated with carbon). The stack 102 also includes a strip of separator material (e.g., a microporous polymer film or a nonwoven fabric mat) disposed between a strip of cathode active material and a strip of anode active material. The cathode, anode, and separator layers may remain flat in a planar configuration or may be rolled up into a wound configuration (e.g., a "jelly roll"). An electrolyte solution is disposed between each cathode and anode.

[0028] During assembly of the battery cell 100, the stack 102 may be enclosed in a container such as a bag or a hard container. The stack 102 may be a planar or wound configuration, but other configurations are also possible. In some variations, the container may be a bag. In such variations, the bag is a flexible sheet folded along a fold line 112. In various aspects, the flexible sheet is made of aluminum with a polymer film such as polypropylene. After folding the flexible sheet, the flexible sheet may be sealed, for example, by applying heat along the side seals 110 and along the platform seals 108. The thickness of the flexible bag may be less than or equal to 120 microns to improve the packaging efficiency of the battery cell 100, the density of the battery cell 100, or both. In other variations, the container is a metal container that can be welded along the seam.

[0029] The stack 102 may also include a set of conductive leads 106 coupled to the cathode and anode. The conductive leads 106 may extend through a seal in the bag (e.g., a seal formed using the sealing tape 104) to provide a terminal for the battery cell 100. The conductive leads 106 may then be used to electrically couple the battery cell 100 to one or more other battery cells to form a battery pack. For example, a battery pack may be formed by coupling battery cells in a series, parallel, or series-parallel configuration. Such coupled cells may be enclosed in a hard case to complete the battery pack, or may be embedded in a housing of a portable electronic device such as a laptop computer, tablet computer, mobile phone, personal digital assistant (PDA), digital camera, and / or portable media player.

[0030] Figure 2 A battery cell 200 (eg, Figure 1 1 . The battery includes: a cathode 202 including a current collector 204 and a cathode active material 206; and an anode 210 including an anode current collector 212 and an anode active material 214. A separator 208 is disposed between the cathode 202 and the anode 210. An electrolyte fluid 216 is disposed between the cathode 202 and the anode 210 and in contact with the separator 208. To form a battery cell, the cathode 202, the separator 208, and the anode 210 may be stacked in a planar configuration, or they may be stacked and then wound into a wound configuration. The electrolyte fluid 216 may then be added. Prior to assembling the battery cell, this set of layers may correspond to a cell stack.

[0031] The cathode current collector, cathode active material, anode current collector, anode active material and separator can be any material known in the art. In some variations, the cathode current collector can be aluminum foil and the anode current collector can be copper foil.

[0032] The cathode active material can be any material known in the art. For example, the cathode active material can be any cathode active material described in U.S. Patent No. 10,297,823, which is incorporated herein by reference in its entirety. By further example, the compound can be any compound of formula (Ia)-formula (VIIIb) of U.S. Patent No. 10,297,823, which is incorporated herein by reference.

[0033] The separator may include a microporous polymer film or a nonwoven fabric pad. Non-limiting examples of microporous polymer films or nonwoven fabric pads include microporous polymer films or nonwoven fabric pads of the following materials: polyethylene (PE), polypropylene (PP), polyamide (PA), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polyester, and polyvinylidene fluoride (PVdF). However, other microporous polymer films or nonwoven fabric pads are also possible (e.g., gel polymer electrolytes). In some variations, the separator may be a separator such as disclosed in U.S. Pat. No. 10,153,474, which is incorporated herein by reference in its entirety.

[0034] In general, a separator refers to a structure in a battery, such as an intercalation layer, that prevents physical contact between the cathode and anode while allowing ions to be transported between the two. The separator is formed of a material having holes that provide ion transport channels (which may include absorbing an electrolyte fluid containing ions). The material used for the separator can be selected based on chemical stability, porosity, pore size, permeability, wettability, mechanical strength, dimensional stability, softening temperature, and thermal shrinkage. These parameters may affect battery performance and safety during operation.

[0035] Generally speaking, the electrolyte fluid can serve as a conductive path for transferring cations from the negative electrode to the positive electrode during discharge. The electrolyte fluid may include any electrolyte fluid known in the art. In various aspects, the electrolyte fluid may be, for example, an electrolyte fluid described in U.S. Patent Application Serial No. 17 / 865,991, which is incorporated herein by reference in its entirety.

[0036] Figure 3A 300 is a side view of an anode 300. Anode 300 includes an anode current collector 302. A first layer 304 including silicon 305 is disposed on the anode current collector 302. A second layer 306 including graphite 307 is disposed on the first layer 304. In contrast, Figure 3B A side view of an anode is depicted, the anode comprising an anode current collector 302 and a single layer 308 comprising both silicon 305 and graphite 307 disposed on the anode current collector 302 .

[0037] In various aspects, the silicon-containing layer and the graphite-containing layer may be present in a weight % ratio. In some variations, the silicon-containing layer is equal to or less than 60 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 55 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 50 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 45 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 40 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 35 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 30 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 25 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 20 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 15 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is equal to or less than 10 weight percent of the total weight percent of the two layers.

[0038] In some variations, the silicon-containing layer is at least 5 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 10 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 15 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 20 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 25 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 30 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 35 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 40 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 45 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 50 weight % of the total weight % of the two layers. In some variations, the silicon-containing layer is at least 55 weight % of the total weight % of the two layers.

[0039] In some variations, the graphite-containing layer is at least 30% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 35% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 40% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 45% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 50% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 55% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 60% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 65% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 70% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 75% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 80% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is at least 85 weight percent of the total weight percent of the two layers. In some variations, the graphite-containing layer is at least 90 weight percent of the total weight percent of the two layers.

[0040] In some variations, the graphite-containing layer is equal to or less than 95% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 90% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 85% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 80% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 75% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 70% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 65% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 60% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 55% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 50% by weight of the total weight % of the two layers. In some variations, the graphite-containing layer is equal to or less than 45 wt % of the total wt % of the two layers. In some variations, the graphite-containing layer is equal to or less than 40 wt % of the total wt % of the two layers. In some variations, the graphite-containing layer is equal to or less than 35 wt % of the total wt % of the two layers.

[0041] In some variations, the silicon-containing layer is 15-25 weight percent of the total weight of the two layers, and the graphite-containing layer is 75-85 weight percent of the total weight of the two layers.

[0042] The layers may also have thicknesses within a range.

[0043] In some variations, the silicon-containing layer is at least 4 μm thick. In some variations, the silicon-containing layer is at least 8 μm thick. In some variations, the silicon-containing layer is at least 10 μm thick. In some variations, the silicon-containing layer is at least 15 μm thick. In some variations, the silicon-containing layer is at least 20 μm thick. In some variations, the silicon-containing layer is at least 25 μm thick. In some variations, the silicon-containing layer is at least 30 μm thick. In some variations, the silicon-containing layer is at least 35 μm thick. In some variations, the silicon-containing layer is at least 40 μm thick. In some variations, the silicon-containing layer is at least 45 μm thick.

[0044] In some variations, the silicon-containing layer is less than or equal to 50 μm thick. In some variations, the silicon-containing layer is less than or equal to 45 μm thick. In some variations, the silicon-containing layer is less than or equal to 35 μm thick. In some variations, the silicon-containing layer is less than or equal to 30 μm thick. In some variations, the silicon-containing layer is less than or equal to 25 μm thick. In some variations, the silicon-containing layer is less than or equal to 20 μm thick. In some variations, the silicon-containing layer is less than or equal to 15 μm thick. In some variations, the silicon-containing layer is less than or equal to 10 μm thick. In some variations, the silicon-containing layer is less than or equal to 8 μm thick.

[0045] In some variations, the graphite layer is at least 2.5 μm thick. In some variations, the graphite layer is at least 3 μm thick. In some variations, the graphite layer is at least 5 μm thick. In some variations, the graphite layer is at least 10 nm thick. In some variations, the graphite layer is at least 15 μm thick. In some variations, the graphite layer is at least 20 μm thick. In some variations, the graphite layer is at least 30 μm thick. In some variations, the graphite layer is at least 40 μm thick. In some variations, the graphite layer is at least 50 μm thick. In some variations, the graphite layer is at least 60 μm thick. In some variations, the graphite layer is at least 70 μm thick. In some variations, the graphite layer is at least 80 μm thick. In some variations, the graphite layer is at least 90 μm thick. In some variations, the graphite layer is at least 100 μm thick. In some variations, the graphite layer is at least 150 μm thick. In some variations, the graphite layer is at least 200 μm thick. In some variations, the graphite layer is at least 250 μm thick. In some variations, the graphite layer is at least 300 μm thick. In some variations, the graphite layer is at least 350 μm thick. In some variations, the graphite layer is at least 400 μm thick. In some variations, the graphite layer is at least 450 μm thick. In some variations, the graphite layer is at least 500 μm thick. In some variations, the graphite layer is at least 550 μm thick. In some variations, the graphite layer is at least 600 μm thick. In some variations, the graphite layer is at least 650 μm thick. In some variations, the graphite layer is at least 700 μm thick. In some variations, the graphite layer is at least 750 μm thick. In some variations, the graphite layer is at least 800 μm thick. In some variations, the graphite layer is at least 850 μm thick. In some variations, the graphite layer is at least 900 μm thick. In some variations, the graphite layer is at least 950 μm thick.

[0046] In some variations, the graphite layer is less than or equal to 1000 μm thick. In some variations, the graphite layer is less than or equal to 950 μm thick. In some variations, the graphite layer is less than or equal to 900 μm thick. In some variations, the graphite layer is less than or equal to 850 μm thick. In some variations, the graphite layer is less than or equal to 800 μm thick. In some variations, the graphite layer is less than or equal to 750 μm thick. In some variations, the graphite layer is less than or equal to 700 μm thick. In some variations, the graphite layer is less than or equal to 650 μm thick. In some variations, the graphite layer is less than or equal to 600 μm thick. In some variations, the graphite layer is less than or equal to 550 μm thick. In some variations, the graphite layer is less than or equal to 500 μm thick. In some variations, the graphite layer is less than or equal to 450 μm thick. In some variations, the graphite layer is less than or equal to 400 μm thick. In some variations, the graphite layer is less than or equal to 350 μm thick. In some variations, the graphite layer is less than or equal to 300 μm thick. In some variations, the graphite layer is less than or equal to 250 μm thick. In some variations, the graphite layer is less than or equal to 200 μm thick. In some variations, the graphite layer is less than or equal to 150 μm thick. In some variations, the graphite layer is less than or equal to 80 μm thick. In some variations, the graphite layer is less than or equal to 70 μm thick. In some variations, the graphite layer is less than or equal to 60 μm thick. In some variations, the graphite layer is less than or equal to 55 μm thick. In some variations, the graphite layer is less than or equal to 50 μm thick. In some variations, the graphite layer is less than or equal to 45 μm thick. In some variations, the graphite layer is less than or equal to 30 μm thick. In some variations, the graphite layer is less than or equal to 25 μm thick. In some variations, the graphite layer is less than or equal to 20 μm thick. In some variations, the graphite layer is less than or equal to 15 μm thick. In some variations, the graphite layer is less than or equal to 10 μm thick. In some variations, the graphite layer is less than or equal to 5 μm thick. In some variations, the graphite layer is less than or equal to 3 μm thick.

[0047] Silicon-containing layer

[0048] The silicon-containing layer may include any silicon compound known in the art. As described herein, silicon may also be referred to as a silicon-containing active material. In various non-limiting examples, silicon may be a silicon-carbon composite, silicon monoxide (SiO x , also referred to herein as "metal oxide"), a silicon metal alloy or a silicon metal oxide. In some variations, the silicon is silicon oxide. The anode active material containing silicon can achieve a higher specific capacity than when it does not contain silicon.

[0049] The silicon-containing layer may include a binder different from the graphite-containing layer. In some variations, the binder is selected from polyacrylic acid (PAA), polyimide (PI), polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyethyleneimine (PI), polyurethane (PU), their derivatives, their copolymers and their combinations. In some variations, the binder is selected from polyacrylic acid (PAA), polyimide (PI), polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyethyleneimine (PI), polyurethane (PU) and their combinations. In some variations, the silicon-containing layer may have a polyurethane binder. In various aspects, the silicon-containing layer may have a polyacrylic binder.

[0050] In some variations, the silicon-containing layer comprises at least 1 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 2 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 3 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 4 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 5 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 6 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 7 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 8 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 9 wt % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 10 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 11 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 12 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 13 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 14 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 15 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 16 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 17 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 18 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises at least 19 weight percent of the binder, based on the total weight percent of the silicon-containing layer.

[0051] In some variations, the silicon-containing layer comprises less than or equal to 20 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 19 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 18 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 17 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 16 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 15 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 14 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 13 weight % of the total weight % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 12 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 11 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 10 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 9 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 8 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 7 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 6 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 5 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 4 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 3 wt % of the total wt % of the silicon-containing layer. In some variations, the silicon-containing layer comprises less than or equal to 2 wt % of the total wt % of the silicon-containing layer.

[0052] In some variations, the first layer may include carbon nanotubes (CNTs), vapor grown carbon fibers (VGCFs), graphite (eg, conductive graphite), carbon black, any one of the foregoing materials alone, or a combination of two or more of the foregoing materials.

[0053] In some additional variations, carbon nanotubes may be added to the silicon-containing layer. In some variations, the CNTs are single-walled CNTs. In some variations, the CNTs are multi-walled CNTs. In some variations, the CNTs may be a combination of single-walled CNTs and multi-walled CNTs.

[0054] In some variations, the CNTs may be at least 0.1% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.2% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.3% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.4% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.5% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.6% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.7% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.8% by weight of the silicon-containing layer. In some variations, the CNTs may be at least 0.9% by weight of the silicon-containing layer.

[0055] In some variations, the CNTs may be less than or equal to 1.0% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.9% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.8% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.7% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.6% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.5% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.4% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.3% by weight of the silicon-containing layer. In some variations, the CNTs may be less than or equal to 0.2% by weight of the silicon-containing layer.

[0056] In some variations, the silicon-containing layer includes CMC. In some variations, CMC is at least 0.1 weight % of the silicon-containing layer. In some variations, CMC is at least 0.2 weight % of the silicon-containing layer. In some variations, CMC is at least 0.3 weight % of the silicon-containing layer. In some variations, CMC is at least 0.4 weight % of the silicon-containing layer. In some variations, CMC is at least 0.5 weight % of the silicon-containing layer. In some variations, CMC is at least 0.6 weight % of the silicon-containing layer. In some variations, CMC is at least 0.7 weight % of the silicon-containing layer. In some variations, CMC is at least 0.8 weight % of the silicon-containing layer. In some variations, CMC is at least 0.9 weight % of the silicon-containing layer. In some variations, CMC is at least 1.0 weight % of the silicon-containing layer. In some variations, CMC is at least 1.1 weight % of the silicon-containing layer. In some variations, CMC is at least 1.2 weight % of the silicon-containing layer. In some variations, the CMC is at least 1.3% by weight of the silicon-containing layer. In some variations, the CMC is at least 1.4% by weight of the silicon-containing layer.

[0057] In some variations, the CMC is less than or equal to 1.5 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 1.4 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 1.5 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 1.2 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 1.1 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 1.0 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.9 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.8 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.7 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.6 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.5 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.4 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.3 wt % of the silicon-containing layer. In some variations, the CMC is less than or equal to 0.2 wt % of the silicon-containing layer.

[0058] Graphite layer

[0059] The graphite-containing layer may include a binder different from the silicon-containing layer. In some variations, the binder is SBR. In some variations, the binder is CMC. In some variations, the binder is a combination of SBR and CMC. Different binders for each active material are used for slurry preparation, and then each material with different binders and / or different amounts of binders is coated separately.

[0060] In some variations, the weight % of SBR is at least 0.5 weight % of the graphite-containing layer. In some variations, the weight % of SBR is at least 1.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is at least 2.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is at least 3.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is at least 4.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is at least 5.0 weight % of the graphite-containing layer.

[0061] In some variations, the weight % of SBR is less than or equal to 6.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is less than or equal to 5.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is less than or equal to 4.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is less than or equal to 3.0 weight % of the graphite-containing layer. In some variations, the weight % of SBR is less than or equal to 2.0 weight % of the graphite-containing layer.

[0062] In some variations, the weight % of CMC is at least 0.1 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 0.5 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 1.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 1.3 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 1.5 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 1.7 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 2.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 3.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is at least 4.0 weight % of the graphite-containing layer.

[0063] In some variations, the weight % of CMC is less than or equal to 5.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 4.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 3.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 2.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 1.7 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 1.3 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 1.0 weight % of the graphite-containing layer. In some variations, the weight % of CMC is less than or equal to 0.5 weight % of the graphite-containing layer.

[0064] In some variations, the weight % of the combination of SBR and CMC is at least 1.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 2.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 3.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 4.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 5.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 6.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 7.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 8.0 weight % of the graphite-containing layer. In some variations, the weight % of the combination of SBR and CMC is at least 9.0 weight % of the graphite-containing layer.

[0065] In some variations, the combined weight % of SBR and CMC is less than or equal to 10.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 9.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 8.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 7.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 6.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 5.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 4.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 3.0 weight % of the graphite-containing layer. In some variations, the combined weight % of SBR and CMC is less than or equal to 2.0 weight % of the graphite-containing layer.

[0066] Figure 4 The capacity of a first battery 402 is plotted as a function of battery cycle number, the first battery being a battery having a structure similar to (having a silicon-containing layer disposed on a copper foil substrate and a graphite-containing layer disposed on the silicon-containing layer) Figure 3A A battery cell with an anode of . Specifically, the anode of battery 402 includes a first layer of 85.00 wt % silicon oxide, 9.80 wt % PU binder, 0.70 wt % binder CMC, 5.00 wt % additive SFG-6L and 0.5 wt % additive SWCNT (single-walled carbon nanotube) disposed on a copper foil substrate, and a second layer of 95.60 wt % graphite with 2.00 wt % SBR binder and 1.30 wt % CMC binder. The anode of the second battery 404 includes a single layer combining both silicon oxide and graphite, which includes 94.21 wt % active material composed of 20 wt % silicon oxide and 80 wt % graphite, 4.71 wt % PU binder, SBR binder and CMC binder composition, 0.14 wt % SWCNT and 0.94 wt % Super P (carbon black). The battery with two anode active materials maintains approximately the same capacity within 28 cycles. However, the cell with both the silicon-containing layer and the graphite-containing layer as the anode active material maintained capacity from cycle 28 to cycle 46. The cell with a single layer of anode active material dropped off precipitously. The two layers of anode active material produced significantly improved cell performance.

[0067] Figure 5A Depicted Figure 3ASEM image of the depicted layers. The image shows a copper current collector 502 , a first layer comprising silicon oxide 504 disposed on the copper current collector 502 , and a second layer of graphite 506 disposed on the first layer comprising silicon oxide 504 . Figure 5B Depicted Figure 3B 506 and silicon oxide 504.

[0068] Fig. 6A Depicted Figure 3A Depicted is an SEM image of a graphite-containing layer lacking any silicon oxide. Specifically, in the image of the graphite-containing layer, only graphite 602 is visible. The image does not show silicon oxide particles. In contrast, Figure 6B Depicts the combined graphite and silicon oxide in a single layer (e.g. Figure 3B 602. It can be seen that silicon oxide particles 604 are dispersed in the graphite 602.

[0069] Fig. 7A Depicted are CNT particles 702 and silicon oxide particles 704 when silicon oxide and graphite are separated in two layers. In a variation, when the same total amount of CNTs is added, the CNTs are more effective when only on the silicon-containing layer. Figure 7B Depicted are CNT particles 702 in a single layer of combined silicon oxide particles 704 and graphite 706. However, when silicon oxide and graphite are combined in a single layer, the CNTs are shared between the graphite and silicon oxide. The CNT particles coat both silicon oxide and graphite in a single layer, rather than just silicon oxide as in a two-layer anode active material.

[0070] Fig. 8A and Figure 8B Both show a comparison of the capacity retention as a function of cycle count for a two-layer anode active material having separate silicon-containing and graphite-containing layers and a single-layer anode active material. Figure 4 Same as depicted. Fig. 8A and Figure 8B , the capacity retention as a function of cycle count is higher for the two layers of anode active material 402 than for the single layer of anode active material 404 .

[0071] Fig. 9 The discharge capacity over various cycle counts for three cells are shown: cell 902, which has an anode having a first silicon-containing layer disposed on the anode and a second graphite-containing layer disposed on the silicon-containing layer; cell 904, which has only a silicon-containing layer; and cell 906, which has only a graphite layer. The results show that the cell with two anode layers exhibits improved electrochemical performance compared to the cell with a single-layer anode.

[0072] The anodes described herein may be valuable in battery cells, including those used in electronic devices and consumer electronics. An electronic device herein may refer to any electronic device known in the art. For example, an electronic device may be a telephone such as a mobile phone and a landline phone, or any communication device such as a smart phone (including, for example, ), and email sending / receiving devices. The electronic device may also be an entertainment device, including a portable DVD player, a conventional DVD player, a Blu-ray player, a video game controller, a music player such as a portable music player (e.g., ), etc. The electronic device may be part of a display such as a digital display, a television monitor, an e-book reader, a portable web browser (e.g., ), a watch (e.g., Apple Watch), or a computer monitor. The electronic device may also be part of a device that provides control, such as controlling the flow of images, video, sound (e.g., Apple ), or it may be a remote control for an electronic device. In addition, the electronic device may be a part of a computer or its accessories, such as a hard drive tower housing or protective case, a laptop housing, a laptop keyboard, a laptop trackpad, a desktop computer keyboard, a mouse, and a speaker. The anode unit, lithium metal battery, and battery pack may also be applied to devices such as watches or clocks.

[0073] For the purpose of explanation, the foregoing description uses specific nomenclature to provide a thorough understanding of the described embodiments. However, it will be apparent to those skilled in the art that specific details are not required in order to practice the described embodiments. Therefore, for the purpose of illustration and description, the foregoing description of the specific embodiments described herein is presented. They are not intended to be exhaustive or to limit the embodiments to the disclosed precise forms. It will be apparent to those of ordinary skill in the art that, in view of the above teachings, many modifications and variations are possible.

Claims

1. An anode, comprising: Anode current collector; a first layer, the first layer being disposed on the anode current collector, the first layer comprising a silicon-containing active material; and A second layer is disposed on the first layer, the second layer comprising graphite. 2 . The anode of claim 1 , wherein the anode current collector comprises copper or nickel.

3. An anode according to any preceding claim, wherein the first layer is 5 wt% to 60 wt% of the total wt% of the first layer and the second layer.

4. An anode according to any preceding claim, wherein the first layer is 10 wt% to 30 wt% of the total wt% of the first layer and the second layer.

5. The anode of any preceding claim, wherein the first layer is 15-25 wt% of the total wt% of the first and second layers.

6. An anode according to any preceding claim, wherein the first layer comprises a first binder.

7. The anode according to claim 6, wherein the first binder is selected from polyacrylic acid (PAA), polyimide (PI), polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyethyleneimine (PI), polyurethane (PU), derivatives thereof, copolymers thereof, and combinations thereof.

8. The anode of claim 7, wherein the first binder comprises polyurethane or polyacrylic acid.

9. The anode of claim 8, wherein the first binder is polyurethane.

10. The anode according to one of claims 6 to 9, wherein the first layer comprises carboxymethyl cellulose (CMC).

11. The anode of any preceding claim, wherein the first layer comprises single-walled carbon nanotubes, multi-walled carbon nanotubes, vapor grown carbon fibers (VGCF), graphite, or carbon black.

12. The anode according to any one of claims 6 to 11, wherein the amount of the first binder is 5 wt% to 20 wt% of the first layer.

13. An anode according to any preceding claim, wherein the second layer comprises a second binder. 14 . The anode of claim 13 , wherein the amount of the second binder is 1 to 10 wt % of the second layer.

15. The anode according to one of claims 13 or 14, wherein the second binder is selected from styrene-butadiene rubber (SBR), CMC and a combination of both.

16. The anode according to one of claims 13 to 15, wherein the second binder is a combination of SBR and CMC.

17. The anode according to one of claims 15 or 16, wherein the amount of SBR is 0.5 wt% to 5 wt%.

18. The anode according to any one of claims 15 to 17, wherein the amount of CMC is 0.5 wt% to 5 wt%.

19. The anode of any preceding claim, wherein the second layer comprises carbon black.

20. A battery cell, comprising: a cathode comprising a cathode active material disposed on a cathode current collector; An anode according to any preceding claim; a separator disposed between the cathode and the anode; and An electrolyte fluid is disposed between the cathode and the anode.

Citation Information

Patent Citations

  • Separators having improved temperature ranges for battery shutdown

    US10153474B1

  • Cathode active materials having improved particle morphologies

    US10297823B2

  • Abuse tolerant electrolyte for lithium-ion battery cells

    US20230092737A1